The Horizontal Curved Geometric Redesign on Jalan Lingkar LIPI Cibinong Using The AutoCADÂ® Civil 3D Method - Addina Kamila Rahmawati; Yusra A Sari (Fakultas Teknik Sipil dan Perencanaan, 2023)
Road geometric planning is one of the requirements for road construction that aims to provide comfort, safety, and speed for road users. In this geometric road planning, the author plans the horizontal curved road geometrics on the Cibinong Lipi Ring Road at STA 0+000 - STA 0+553.46, located in Bogor Regency, West Java Province, by using AutoCADÂ® Civil 3D auxiliary program. This research uses quantitative methods by taking data from Google Earth and Global Mapper. The steps in this research include terrain classification, road trajectory planning, horizontal alignment planning, design planning criteria, and bend design. The design results show that the Lingkar Lipi Cibinong Road is a Primary local road class III, with a 2/2 TT road type. On this road, the geometric horizontal alignment is designed with two bend designs using the Full Circle (F-C) bend type with a radius of 151 m and SCS (Spiral - Circle - Spiral) with a radius of 165 m, plan speed (Vr) 60 km/h, maximum superelevation of 8%.